Endovascular repair of ascending aortic diseases with custom-made endografts. (4th January 2021) - Piffaretti, Gabriele; Czerny, Martin; Riambau, Vicente; Gottardi, Roman; Wolfgruber, Thomas; Probst, Chris; Matt, Peter; Antonello, Michele; Gerosa, Gino; Hamady, Mohamad; Fontana, Federico; Ferrarese, Sandro; et al.
Abstract:  : OBJECTIVES: The aim of this article is to report the mid-term results of ascending thoracic endovascular aortic repair using a custom-made device (CMD). METHODS: This was a retrospective study performed at tertiary centres. Nine patients considered unfit for open surgery received elective total endovascular repair of the ascending aorta with a Relay ® (Terumo Aortic, Sunrise; FL, USA) CMD: pseudoaneurysn ( n = 5), localized dissection ( n =3) and contained rupture ( n = 1). RESULTS: Primary clinical success was achieved in all patients with no major complications and no early conversion to open surgery. All patients were discharged home and independent: median length of stay was 7 days (interquartile range, 6–18). No patient was lost to follow-up at a median 26 months (interquartile range, 12–36). Three patients died 2, 6 and 24 months after intervention; 1 was aorta related (late aorto-atrial fistula due to infection that required open surgery). At the last follow-up available, no endoleaks, migrations, fractures or ruptures were observed in the remaining 6 patients. CONCLUSIONS: Ascending thoracic endovascular aortic repair with Terumo Aortic CMDs was technically feasible, effective and safe in very selected lesions. CMDs showed good ascending aorta conformability with different configurations and diameters, and satisfactory mid-term durability as shown by both structural integrity and aortic lesion exclusion.